2021
DOI: 10.2147/jir.s311518
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Dysbiosis Correlates with Abnormal Immune Response in Moderate COVID-19 Patients with Fever

Abstract: Background Most COVID-19 patients are moderate, and fever is the most common clinical manifestation and associated with poorer prognosis. Gut microbiota may also play important roles in COVID-19 pathogenesis. However, the association between gut microbiota and fever in individuals with moderate COVID-19 remains unclear. Methods We compared the clinical features and laboratory results of 187 moderate COVID-19 patients with fever and without fever and identified several i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 40 publications
4
38
1
Order By: Relevance
“…Furthermore, dysbiosis due to declined Bacteroides spp. the population was positively correlated with D-dimer, neutrophils, IL-6, CRP, and LDH in acute and long-term COVID infection [ 127 ].…”
Section: Gut Microbiota Diversity With Crp and Other Severity Biomark...mentioning
confidence: 99%
“…Furthermore, dysbiosis due to declined Bacteroides spp. the population was positively correlated with D-dimer, neutrophils, IL-6, CRP, and LDH in acute and long-term COVID infection [ 127 ].…”
Section: Gut Microbiota Diversity With Crp and Other Severity Biomark...mentioning
confidence: 99%
“…However, the impact of acute fever responses on the mammalian microbiota is relatively unknown. A recent study found that patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-Cov2) show fever-dependent shifts in the gut microbiota, including an increase in bacterial heat shock proteins, suggesting that fever temperatures do impact the human microbiome ( 58 ).…”
Section: Immunological Heat Stress and The Intestinal Microbiomementioning
confidence: 99%
“…Patients with fever had a significant different gut microbiota composition than those who did not have a fever. Patients with fever had higher opportunistic infections, including Enterococcus faecalis and Saccharomyces cerevisiae [ 139 ]. In the cross-sectional study conducted by Gu et al ., it was discovered that the microbiological profile of COVID-19 patients differed from that of patients with influenza A and healthy controls.…”
Section: Gut Microbiota and Immune System In Covid-19mentioning
confidence: 99%